The relationship of clinical and morphological parameters with the BRAF status of the tumor in patients with stage I skin melanoma - K. S. Titov; M. V. Sorokina; S. S. Lebedev; D. N. Grekov; E. Yu. Neretin; T. A. Yakusheva (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Aim: to study the relationship between clinical and morphological parameters of skin melanoma and the BRAF status of the tumor in patients with stage I of the disease. Materials and methods. The study was retrospective and included 200 patients with stage I skin melanoma (pT1-2aN0M0), of which BRAF status was assessed in 88 patients. All patients underwent clinical data analysis, an extended morphological study and a molecular genetic study to determine the BRAF V600E mutation in the primary tumor. Results. The median age of patients in the total sample was 61.5 years. Mutation in the BRAF V600E gene was detected in 25 patients (28.4%). Patient age, tumor location and Breslow thickness were recognized as independent predictors of BRAF status of stage I skin melanoma. With an increase in the patient's age by 1 year, the chance of having a BRAF V600E mutation decreased by 3.4% or 1.04 times (OR = 0.966; 95% CI = 0.935–0.999; p = 0.045). When melanoma was localized in the lumbar region, the chance of having a BRAF V600E mutation increased by 15.311 times (95% CI = 1.239–189.142; p = 0.033). With a tumor thickness according to Breslow of more than 0.7 mm, the chance of having a BRAF V600E mutation increased by 2.939 times (95% CI = 1.031-8.376; p = 0.044). With a threshold value of the logistic function of 50%, the sensitivity and specificity of the proposed model were 28.0% and 93.7%, respectively. When the threshold function value is reduced to 25.3%, the sensitivity of the model increases to 68% with a simultaneous drop in specificity to 61.9%. Conclusion. Younger age, greater tumor thickness according to Breslow, and tumor localization in the lumbar region in patients with stage I skin melanoma increase the chance of having a BRAF V600E mutation, while other morphological parameters of the tumor are not associated with BRAF status. However, moderate sensitivity does not allow for a sufficiently accurate determination of the presence of a mutation, thereby strengthening the belief in the need for molecular genetic testing.